The Effect of Plyometric Training On the Development of Power Defined By Speed and The Speed of Passing In 400m Hurdles For Advanced Men - Mohameed, Ahmed (Journal of Physical Education, 2016)
The aim of the research is to design exercises for developing power defined by speed and passing speed in 400m hurdles for men. The problem of the research lies in making training programs that lack muscular strength training that affected the level of achievement in hurdles throughout the years. The researchers hypothesized statistical differences between pre and posttests in power defined by speed and passing speed. The researcher used the experimental method. The subjects were (6) hurdles. Two power defined by speed tests were applied; (5) hurdles test and 400m hurdles tests. The pretests were applied followed by the training program that consisted of (8) weeks with (3) training sessions per week. The researcher concluded that plyometric exercises are effective in developing power defined by speed, passing speed and improving achievement. The results also showed that training efforts improved the strength of running between hurdles.